High Intensity Interval Training and Arterial Hypertension: Quality of Reporting - Bünzen, Claudia; Oberbeck, Kaija; Ketelhut, Sascha; Weisser, Burkhard (Sports Medicine International Open, 2025)
The benefits of exercise have been well described for the treatment of hypertension. Poor reporting quality impairs quality appraisal and replicability. High intensity interval training (HIIT) has been shown to be an effective alternative to traditional aerobic exercise in patients with hypertension. We evaluated the completeness of reporting of randomized controlled trials (RCTs) with HIIT for hypertension and to compare both exercise modes in reporting quality. RCTs of HIIT with a minimum duration of 6 weeks in adults with at least high normal blood pressure (≥130 mmHg/≥85 mmHg) were evaluated using the Consensus on Exercise Reporting Template (CERT). Nine RCTs conducting HIIT in hypertensive patients (N=718; 51.8 years) were evaluated. A mean of 62.6% of items were sufficiently described, compared with 49.2% in moderate intensity training interventions. Exercise dose was adequately reported in 8 out of 9 studies. Only one study reported information on adverse events. In a small sample of RCTs with HIIT in patients with hypertension we found a better reporting quality than in moderate intensity training interventions. However, reporting completeness is not optimal for a good replicability in clinical practice. The lack of reporting of adverse events in interventions using high intensities is particularly unfavourable.
Keywords: reporting quality; clinical practice; CERT checklist; interval training; high blood pressure